Evaluating the Mediating Role of Transformational Leadership in the Nexus of Employee Motivation, Engagement, Emotional Intelligence, and Performance: A Comprehensive Review - Baomar S.M.; Islam M.K. (World Scientific and Engineering Academy and Society, 2025)
This study aims to examine the impact of transformational leadership on employee performance in Oman's telecoms industry. This research is driven by the necessity for companies to enhance staff productivity in order to gain a competitive advantage. The study conducts a thorough examination of previous literature to explore the influence of employee motivation, engagement, and emotional intelligence on performance. Moreover, it assesses the ability of transformational leadership to serve as a vital link in improving employee outcomes. The research will offer managers and executives in the telecom industry useful suggestions to help them create strategies that will boost productivity and accomplish organizational objectives. The study provides specific goals and research questions to direct further studies in this area. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.